Pengaruh Harga Dan Lokasi Terhadap Keputusan Pembelian Konsumen Pedagang Kaki Lima Jalan Garuda Wekke’e - Sariwana, Sariwana (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
Business competition between business actors is currently increasingly fierce, namely competition that increasingly tends to change in technology. Street vendors on Jalan Garuda Wekke'e are business actors who need to innovate marketing strategies to increase their sales turnover by understanding the factors that influence consumer purchasing decisions. The emergence of consumers shopping on sidewalks has resulted in a lack of shoppers in shopping centers. The formulation of the problem in this research is whether there is an influence of price and location on consumer purchasing decisions of street vendors on Jalan Garuda Wekke'e. The aim of this research is to determine the influence of price and location on consumer purchasing decisions of street vendors. This research is quantitative research. The population used in this research is consumers who have/have shopped at street vendors on Jalan Garuda Wekke'e. The sample for this research was 50 respondents, taken using the Non-Probability Sampling technique with an accidental sampling approach. The analytical methods used include validity and reliability tests, classical assumption tests, multiple regression analysis, hypothesis testing via the t test and f test, as well as analysis of the coefficient of determination (R2). The results of the research show that: Price has no influence on purchasing decisions. Location has a positive effect on purchasing decisions. Meanwhile, together (simultaneously) the Price and Location variables have a positive influence on the Purchasing Decision variable.